2018
DOI: 10.17531/ein.2018.1.10
|View full text |Cite
|
Sign up to set email alerts
|

On System Reliability of Increasing multi-state linear k-within-(m,s)-of-(m,n):F lattice system

Abstract: A “multi-state linear k-within-(m,s)-of-(m,n):F lattice system” (MS L(k,m,s,n:F)) comprises of m×n components, which are ordered in m rows and n columns. The state of system and components may be one of the following states: 0, 1, 2, …, H. The state of MS L(k,m,s,n:F) is less than j whenever there is at least one sub-matrix of the size m×s which contains kl or more components that are in state less than l for all j ≤ l ≤ H. This system is a model for many applications, for example, tele communication, radar d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Compound 6c inhibits α-glucosidase in vitro with IC 50 of 6.50 μm and exceeds hypoglycemic activity of acarbose in streptozotocin-induced diabetic rats. Recently, structurally related 2-arylbenzo[b]furans [39] and oxadiazolesubstituted benzofurans [40] have been reported as potent inhibitors of α-glucosidase. However, animal studies were not reported to support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 6c inhibits α-glucosidase in vitro with IC 50 of 6.50 μm and exceeds hypoglycemic activity of acarbose in streptozotocin-induced diabetic rats. Recently, structurally related 2-arylbenzo[b]furans [39] and oxadiazolesubstituted benzofurans [40] have been reported as potent inhibitors of α-glucosidase. However, animal studies were not reported to support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Levitin modeled the LCCS considering the nodes allocation such as service nodes [16], series parallel nodes [14] and standby nodes [15]. Other researchers also studied the radio communication LCCS optimization methods by considering different situations, such as random repair time as well as different repair polices [42], multistate components [44] and topological structures [39].…”
Section: Introductionmentioning
confidence: 99%